Frecuencia del análisis de Troponina I cardiaca, en personas atendidas en el laboratorio Quintanilla-Trujillo, abril 2021-abril 2022 - Chacon Guarniz, Yessica Esmeralda (2023)
The present thesis report aims to determine the frequency of cardiac Troponin I analysis performed in people attended at the Quintanilla-Trujillo laboratory, April 2021-April 2022. The database system used by the laboratory to register patients was accessed. The sample consisted of 159 adult patients of both sexes, the quantitative determination of cardiac Troponin I (cTnI) protein was performed using the immunoassay analyzer (MAGLUMI 800) based on the sandwich-type chemiluminescence (CLIA) principle. The results are shown in tables and respective graphs considering: sex, age group and clinical values. From the analysis of the results it can be concluded that of the total number of people who underwent the analysis, the frequency by age was higher in the 61 to 80 years of age with 22.01% of the male sex and 15.09% of the female sex. The high values according to age group were greater in the ages between 41 and 60 years with a percentage of 32.7%; according to sex it was greater in the male than in the female with a percentage of 54.72% and 27.04% respectively.